Захист прав творців реклами від неправомірного використання рекламних матеріалів - Ульянова, Галина Олексіївна; Ульянова, Галина Алексеевна; Ul'janova, Galina (My University, 2012)
The article devoted to comprehensive analysis the legislation, which sets limits on the illegal use of advertising. The author elucidates the peculiarities of copyright protection in the legal relations arising from advertisement.
Ульянова Г. О. Захист прав творців реклами від неправомірного використання рекламних матеріалів / Г. О. Ульянова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Т. 12. – С. 360-369.
Keywords: реклама; автор реклами; виробник реклами; замовник реклами; неправомірне використання реклами; захист прав інтелектуальної власності; автор рекламы; производитель рекламы; заказчик рекламы; неправомерное использование рекламы; защита прав интеллектуальной собственности; advertisement; author of advertisement; producer of advertisement; customer of advertisement; illegal use of advertisement; protection of intellectual property rights